Determinants of Physical Health Self-Management Behaviours in Adults With Serious Mental Illness: A Systematic Review - Coventry, Peter A.; Young, Ben; Balogun-Katang, Abisola; Taylor, Johanna; Brown, Jennifer V. E.; Kitchen, Charlotte; Kellar, Ian; Peckham, Emily; Bellass, Sue; Wright, Judy; Alderson, Sarah; Lister, Jennie; et al. (Frontiers in Psychiatry, 2021)
Behavioural interventions can support the adoption of healthier lifestyles and improve physical health outcomes, but it is unclear what factors might drive success of such interventions in people with serious mental illness (SMI). We systematically identified and reviewed evidence of the association between determinants of physical health self-management behaviours in adults with SMI. Data about American Association of Diabetes Educator’s Self-Care Behaviours (AADE-7) were mapped against the novel Mechanisms of Action (MoA) framework. Twenty-eight studies were included in the review, reporting evidence on 104 determinant-behaviour links. Beliefs about capabilities and beliefs about consequences were the most important determinants of behaviour, especially for being physically active and healthy eating. There was some evidence that emotion and environmental context and resources played a role in determining reducing risks, being active, and taking medications. We found very limited evidence associated with problem solving, and no study assessed links between MoAs and healthy coping. Although the review predominantly identified evidence about associations from cross-sectional studies that lacked validated and objective measures of self-management behaviours, these findings can facilitate the identification of behaviour change techniques with hypothesised links to determinants to support self-management in people with SMI.